2005
DOI: 10.1086/430378
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiologic Comparison of 2 Unusual Clusters of Group A Streptococcal Necrotizing Fasciitis in Hawaii

Abstract: Two clusters of necrotizing fasciitis (NF) due to group A streptococcus (GAS) were identified on the Hawaiian islands of Kauai and Maui during 1997 and 2002, respectively. The emm gene sequence types and the pulsed-field gel electrophoresis patterns were determined for 6 isolates recovered from patients with NF and for 116 isolates recovered from patients with temporally associated community-acquired GAS infection. No predominant emm type was identified, and the emm types of 64 (52.5%) of the isolates were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Previously, we reported that uncommon emm types were observed among patients with invasive and noninvasive GAS infections in Hawaii when compared with the published studies and available CDC data from the mostly sterile site continental U.S. GAS isolates (3, 12, 14, 16, 17). These earlier studies were done in limited number of isolates (< 150 isolates) collected during and following two community-associated necrotizing fasciitis clusters (3, 4).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previously, we reported that uncommon emm types were observed among patients with invasive and noninvasive GAS infections in Hawaii when compared with the published studies and available CDC data from the mostly sterile site continental U.S. GAS isolates (3, 12, 14, 16, 17). These earlier studies were done in limited number of isolates (< 150 isolates) collected during and following two community-associated necrotizing fasciitis clusters (3, 4).…”
Section: Introductionmentioning
confidence: 92%
“…These earlier studies were done in limited number of isolates (< 150 isolates) collected during and following two community-associated necrotizing fasciitis clusters (3, 4). In the current report, we determined the GAS emm types in a larger sample of isolates collected over a period of six years and examined the association between the specific/unique GAS types and clinical manifestations in Hawaii.…”
Section: Introductionmentioning
confidence: 99%
“…The erythromycin resistance rate (ϳ3%) has been low among group A streptococcus (GAS) isolates in Hawaii, where impetigo, acute rheumatic fever, and clusters of necrotizing fasciitis have been reported (5)(6)(7)(8)(9)(10); G. Erdem, G. Matsuura, G. Wheelen, C. Mizumoto, D. Esaki, and P. V. Effler, presented at the XVIIth Lancefield International Symposium on Streptococci and Streptococcal Diseases, Porto Heli, Greece, 2008). During a retrospective survey of 250 GAS cultures collected from patients with invasive GAS disease identified between the years 2005 and 2007, the reviews of the clinical information incidentally showed erythromycin and clindamycin resistance in five patients.…”
mentioning
confidence: 99%
“…infrequently identified in the continental United States are more frequently identified in Hawaii [20], we sought to investigate whether these types have any temporal association with the onset of ARF. To determine if the emm types identified in patients with ARF in Hawaii were frequently observed among the general population, we used a large convenience sample of GAS that was isolated during the study period.…”
mentioning
confidence: 99%